Reducing audible spectral discontinuities. - Klabbers, E.
A common problem in diphone synthesis is discussed, viz., the occurrence of audible discontinuities at diphone boundaries. Informal observations show that spectral mismatch is the most likely the clause of this phenomenon. We first set out to find an objective spectral measure for discontinuity. To this end, several spectral distance measures are related to the results of a listening experiment. Then, we studied the feasibility of extending the diphone database with context-sensitive diphones to reduce the occurrence of audible discontinuities. The number of additional diphones is limited by clustering consonant contexts that have a similar effect on the surrounding vowels on the basis of the best performing distance measure. A listening experiment has shown that the addition of these context-sensitive diphones significantly reduces the amount of audible discontinuities
Keywords: Audible spectral discontinuities reduction; Consonant contexts clustering; Context-sensitive diphones; Diphone boundaries; Diphone database; Diphone synthesis; Listening experiment; Objective spectral measure; Spectral distance measures; Spectral mismatch; Vowels